3х(х-4)=(х+2)(3х-3) (5х-1)(х+2)-5(х-4)(х-2)=0

0
0

3х(х-4)=(х+2)(3х-3) (5х-1)(х+2)-5(х-4)(х-2)=0

0
0

Ответ:

Объяснение:

1)

раскрываем скобки

3x^2-12x=3x^2-3x+6x-6

сократим 3x^2 и 3x^2

-12x=-3x+6x-6

неизвестные влево. известные вправо

-12x+3x-6x=-6

-15x=-6

x=-6:(-15)

x=0,4

2)

раскрываем скобки

5x^2+10x-x-2-5(x-4)*(x-2)=0

5x^2+10x-x-2-5x^2+10x+20x-40=0

cокращаем 5x^2 и -5x^2

10x-x-2+10x+20x-40=0

неизвестные влево, известные вправо

10x-x+10x+20=2+40

39x=42

x=42:39

x= дробь 14/13

Показано 1 результата